Growing through the merger and acquisition - XU, Jianhuan (Institutional Knowledge at Singapore Management University, 2017)
The paper studies with an endogenous growth model how the merger and acquisition (M&A) affects the aggregate growth rate. We model the M&A as a capital reallocation process, which can increase both productivity and growth rates of firms. The model is tractable and greatly consistent with patterns observed in the M&A at the micro level. Matching our model to the data, we find that prohibiting the M&A would lead to the reduction of the aggregate growth rate of US economy by 0.1% and the reduction of the aggregate TFP by 5%.